2012
DOI: 10.2174/1874210601206010126
|View full text |Cite
|
Sign up to set email alerts
|

Current Aspects on Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma is the most common malignant epithelial neoplasm affecting the oral cavity. This article overviews the essential points of oral squamous cell carcinoma, highlighting its risk and genomic factors, the potential malignant disorders and the therapeutic approaches. It also emphasizes the importance of the early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
310
1
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(350 citation statements)
references
References 49 publications
2
310
1
12
Order By: Relevance
“…Ever use of alcohol was associated with a 1.67 fold increased risk of oral cancer (Anantharaman et al, 2014). However, it is not proved that alcohol use is the risk of OSCC with adjusted p-value 0.063 in our study, which is different from other studies in other countries (Zygogianni et al, 2011;Markopoulos, 2012). It was shown in this study tobacco use and alcohol consumption had a synergistic effect on the development of OSCC in HPV-positive patients.…”
Section: Li-li Gan Et Alcontrasting
confidence: 98%
See 2 more Smart Citations
“…Ever use of alcohol was associated with a 1.67 fold increased risk of oral cancer (Anantharaman et al, 2014). However, it is not proved that alcohol use is the risk of OSCC with adjusted p-value 0.063 in our study, which is different from other studies in other countries (Zygogianni et al, 2011;Markopoulos, 2012). It was shown in this study tobacco use and alcohol consumption had a synergistic effect on the development of OSCC in HPV-positive patients.…”
Section: Li-li Gan Et Alcontrasting
confidence: 98%
“…But there is some other controversial definitions need to be clarified. In many documents, scientists tend to classified base of tongue into oropharyngeal and focus on the oropharyngeal squamous cell cancer (Herrero et al, 2003;D'Souza et al, 2007), whereas in other countries, authors tend to classified all oral anatomic site into the oral cancer which included oral cavity and oropharyngeal (Pintos et al, 2008;Markopoulos, 2012). Here, we prefer to the latter classification.…”
Section: Li-li Gan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Markopoulos (8) reported that older males, ethnic minority groups and lower socioeconomic groups were more commonly affected by buccal SCC. In the present study, we demonstrated that 38.8% of the patients had a history of alcohol consumption, 61.3% had a history of tobacco product consumption and all patients belonged to low socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma, a cancer of the oral cavity, is one of the ten most common malignant neoplasms and is the 5 th most frequent cancer worldwide (Markopoulos, 2012). The development of oral cancer is usually preceded by distinct precancerous lesions such as leukoplakia, erythroplakia and oral submucous fibrosis.…”
Section: Introductionmentioning
confidence: 99%